Socha viejo - Boyacá. Un monumento histórico en el olvido (2019)
This article is about Sacha Viejo, it is currently a hamlet that is part of Sacha, which is the capital of the province of Valderrama. The study problem starts with the formation of the territory of Sacha Viejo from the pre-Hispanic settlements, the Hispanic foundation, to the hamlet in which today this municipality became due to the landslide and disinterest, which threatens its disappearance constantly. Contrast this, considering the book, "The Allegory of Heritage" by Francoise Choay, the definition of Historical Monument and the two dimensions that constitute it as such: the historical dimension and the artistic or visual dimension. This work is the result of a teaching - learning process developed in the Master on Management of Heritage for Territorial Development of the Santo Tomás University section Tunja, in the module of Foundations of Heritage wehere the "Territory and heritage, its origing and his memories".